Energy Transition and Urban Planning for Local Development. A Critical Review of the Evolution of Integrated Spatial and Energy Planning - Paolo De Pascali (Energies, 2018)
The aim of the article is to analyse the evolution of spatial and energy planning integration, seen as a mean to foster local development, from the birth of the theme to the current prospects of shared sustainability and Decentralised Energy System (DES) solutions. The paper is a review of the evolution of the spatial and energy planning integration, exploring weaknesses and future opportunities. After an initial period of intense theoretical elaboration, the relationship between energy and city physical-functional organization and planning is still far from finding an implementation. The article explains this lack of integration through the analyses of significant steps in the last 50 years with the aim to outline current obstacles in achieving a more comprehensive vision of energy and spatial planning. The experiences selected highlight critical aspects concerning the trend towards the divergence of energy planning from systemic urban and spatial planning, also due to the low consideration of energy as a factor for local development. From the processes of decentralization and energy localism, some perspectives emerge which converge on the eco-energy district as a projection of the local energy community and which seem to enhance a more systemic and strategic dimension of planning.